Thermodynamic analysis of a dual pressure HRSG in combined cycle gas turbine - Sara Nur Imani; Bahsan, Rosnadiah; Tijani, Alhasan Salami; Muritala, Ibrahim Kolawole (UiTM Press, 2025)
Combined cycle gas turbine (CCGT) power plants are recognised as more efficient and lower environmental impact than traditional thermal power plants. The heat recovery steam generator (HRSG) is one of the components in the CCGT plant that converts waste heat from the gas turbine exhaust and uses it to produce steam to generate additional power in the steam turbine, significantly improving the plant’s overall efficiency. Most studies on CCGT power plants have predominantly concentrated on gas turbines, with less emphasis on the HRSG. This study presents a comprehensive thermodynamic analysis of a dualpressure HRSG operating in a CCGT. The analysis was conducted using actual plant data and a steady state energy balance approach to investigate the influence of operating parameters such as pinch and approach point temperature differentials, inlet flue gas temperature, and steam pressure on HRSG performance. Results show that reducing both pinch and approach points enhances heat transfer efficiency and increases HRSG effectiveness. Raising the inlet flue gas temperature from 400 C to 700 C increased HRSG effectiveness from 70% to 86% and lowered the stack temperature from 137 C to 118 C, indicating improved exhaust heat utilization. Best performance was obtained at 70% of design steam pressure, reducing exhaust losses and improving heat recovery. The findings demonstrate that parametric variation of operating parameters can substantially enhance HRSG performance and overall CCGT power plants' efficiency for sustainable power generation.